Merencakanakan Konsep Pondasi Untuk Semua Tipe Bangunan Gedung (Eduscotech, 2024)
Foundations are the basis of a building. The availability of a strong and sturdy foundation will greatly help the longevity of the building. Therefore, the foundation must be a priority in planning, because the foundation has the role and function of bearing all the loads of the building structure above it which is then transmitted to the ground. This journal aims to provide insight to everyone and especially business people in the property sector, so that when planning construction, you must pay attention to the technical aspects of the building that will be built on it. The method in preparing this journal is descriptive research with qualitative methods. Based on the description in this study, the author concludes several important things in planning foundations. Good foundation planning meets 4 criteria: a. Efficient in costs b. Effective in heavy structures c. Optimal in terms of time and method of implementation d. Efficient in building operation and maintenance.    The choice of foundation model must pay attention to the soil bearing capacity aspect. Soil bearing capacity refers to the soil's ability to withstand structural loads. Analyze the bearing capacity of the soil to prevent shear failure or excessive foundation settlement.